The Relationship Between Macroeconomic Factors and Mortgage Market Growth in Kenya - Owuor, Natalie Diana; Githii, Wainaina; Mwangi, Mirie (European Scientific Journal, ESJ, 2018)
The mortgage market is the market for financing real estate assets. Mortgage financing is vital in financing the property market. This study seeks to determine the relationship between selected macro factors and mortgage market growth in Kenya. The study is based on the arbitrage pricing theory, capital assets pricing theory, title theory and lien theory of mortgages. The study utilizes descriptive research design and quarterly secondary data for a period of 10 years from 2007 to 2016. Analysis of data is carried out through descriptive and inferential statistical techniques. Inferential statistics such as linear correlations and multiple linear regressions are used to draw conclusions and make predictions on the relationship between the independent variables and the dependent variable. The research establishes that there is a positive and significant relationship between interest rates, inflation and the mortgage market growth. The research also finds that there is insignificant relationship between exchange rates, gross domestic product and the mortgage market growth. The research concludes that the mortgage market growth in Kenya is influenced by interest rates and inflation. The research recommends that the central bank of Kenya should ensure that interest rates are stable and inflation levels are low to ensure that they do not affect the mortgage market growth.